DETERMINATION OF PHASE COMPOSITION OF ALUMINOTHERMAL BLENDS FOR BORATING - B. B. Hina; N. G. Kuhareva; V. F. Protasevich (Литьë и металлургия, 2010)
The phase composition of aluminothermic borating blends is established using thermodynamic modeling, and also substances, which are the sources of boron atom at subsequent chemicalthermal processing of synthesized environments are sources of boron atoms, are determined.